Stratification & sampling of electricity supply customers for outage costs survey - Hashim A.H.; Hussien Z.F.; Sen D.A.; Chahil H.S.; Abdullah M.Y.; Mohamad M. (2023)
In today's demanding business environment, determining the Value of Lost Load (VoLL) is important in order for utilities to make the right decision when it embarks on any form of asset expansion or assesses risks in power system operation. The VoLL is the aggregated or average value of outage costs across the whole range of customers in the electricity supply industry (ESI). This paper covers the initial process in determining the VoLL from customer survey data. It discusses the data stratification method used to categorize customers according to a set of criteria and then the normalization process of customer survey data. Finally, a demonstration of the stratification method on domestic customers is shown and evaluated. 2006 IEEE.